Polypyrrole-pen ink/polydopamine electrode for flexible all-in-one supercapacitor - Xin, Qing; Hu, Danni; Yan, Wensheng; Zang, Yue; Lin, Jun (Ionics, 2022)
Flexible supercapacitors are recently of extensive interest for flexible electronic devices. Cost and ionic diffusion efficiency between interface of electrode and electrolyte are two key factors that affect their practical application. Here, we report an effective polypyrrole-pen ink/polydopamine (PPy-ink/PDA) film electrode fabricated by in-situ polymerization method. The contribution of diffusion-dominated and surface-dominated processes in charge energy storage process of PPy-ink/PDA film electrode is discussed. Moreover, based on polyvinyl alcohol/polyethylene glycol (PVA/PEG) electrolyte, a flexible all-in-one solid supercapacitor is constructed. Due to the interfacial reaction improved by PDA, the obtained device delivers a high energy density of 12.6 µWh/cm 2 at a power density of 80 µW/cm 2 . In addition, the facile fabrication method of the electrode and low cost of commercial pen ink make it an excellent candidate for flexible electronic devices. Graphical abstract